2000
DOI: 10.1016/s0037-0738(00)00026-9
|View full text |Cite
|
Sign up to set email alerts
|

Composition of modern stream sand derived from a mixture of sedimentary and metamorphic source rocks (Henares River, Central Spain)

Abstract: The Henares River, central Spain, flows westward from the Iberian Range (Mesozoic sedimentary rocks) under semi arid climatic conditions, In the middle and lower reaches, the Henares River receives sediment from three tributaries E-mail addresses:arribas@eucmax.sim.ucm.es(J.Arribas).critelli@irpi.cs.cnr.it(S.Critelli).lepera@irpi.cs.cnr.it (E. Le Pera) , Henares sand composition takes place by the mixing of tributary deposits with previously deposite d Henares River terraces. Abrasion during transport does not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 27 publications
1
38
1
1
Order By: Relevance
“…5c,d) indicate the preservation of feldspars towards the top of the Somosaguas succession, and a remarkable increase in plagioclase grains towards the T3 unit. Contrary to what we might expect for distal sediments (Breyer and Bart, 1978;Mack, 1978;Cavazza et al, 1993;Ingersoll et al, 1993;Arribas et al, 2000), T2 shows no significant reduction in rock fragments and feldspars relative to the other units. This could reflect the fact that increasing aridity will help preserve a higher percentage of feldspar and rock fragment grains.…”
Section: Provenance and Geotectonic Settingcontrasting
confidence: 78%
See 2 more Smart Citations
“…5c,d) indicate the preservation of feldspars towards the top of the Somosaguas succession, and a remarkable increase in plagioclase grains towards the T3 unit. Contrary to what we might expect for distal sediments (Breyer and Bart, 1978;Mack, 1978;Cavazza et al, 1993;Ingersoll et al, 1993;Arribas et al, 2000), T2 shows no significant reduction in rock fragments and feldspars relative to the other units. This could reflect the fact that increasing aridity will help preserve a higher percentage of feldspar and rock fragment grains.…”
Section: Provenance and Geotectonic Settingcontrasting
confidence: 78%
“…However, as several authors have suggested (Palomares and Arribas, 1993;Le Pera and Arribas, 2004), the abundance of these grains in the sediments is not directly related to their abundance in the source area. Even when each lithology have a different Sand Generation Index (Palomares and Arribas, 1993;Arribas et al, 2000;, we can define the extent of intervention of each lithology in the final mixture based on other features. For example, a drop is produced in the Lm/Rt index indicating a smaller contribution of low-grade metamorphic rocks towards the top of the sedimentary succession.…”
Section: Provenance and Geotectonic Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, we have noted a poor representation of Ls grains in the sands (LmLvLs%Ls) compared with source lithology, out lined by a depletion of these grains from source to sand, evaluated on the order of more than half, when compared to the percentages of areal extent in the drainage areas. This is due to the poor capability of sedimentary rocks to generate lithic sand (e.g., Zuffa, 1987;Cavazza et aI., 1993;Arribas et al. 2000) or rapid destruction of sedimentary lithic grains during transport (e.g., Ingersoll et aI., 1993).…”
Section: Province Dmentioning
confidence: 99%
“…The chemical and minero-petrographical features of the sandstone and mudrock samples are considered to be dependent on sedimentary processes, including source rocks, weathering, sorting and tectonic setting (e.g., Arribas et al, 2000;Critelli et al, 2003;Perri et al, 2011. By combining the information deduced from the petrography and chemistry it is possible to decipher the sedimentary evolution and geological processes affecting sediments and, thus, the relationships between the source area and the sedimentary basin (e.g., Critelli et al, 1990;Critelli & Le Pera, 1995;Perri, 2014;Perri & Ohta, 2014).…”
Section: Introductionmentioning
confidence: 99%